Effect of interparticle interaction on magnetic hyperthermia: homogeneous spatial distribution of the particles - Abu-Bakr, Ali Fathi (Philos Trans A Math Phys Eng Sci, 2019)
The paper deals with the theoretical study of the effect of magnetic interparticle interaction on magnetic hyperthermia, produced by the particles under the action of a linearly polarized oscillating field. The particles are homogeneously distributed and immobilized in a rigid medium. The supposed size of the magnetite particles is about 20–30 nm. For these particles, the characteristic time of the Neel remagnetization is much longer than the time of observation. This is why we concluded that the dissipation occurs as a result of the particle magnetic moment oscillation in the pit of energy of magnetic anisotropy. This article is part of the theme issue ‘Heterogeneous materials: metastable and non-ergodic internal structures’.